Predictors of Poststroke Aphasia Recovery: A Systematic Review-Informed Individual Participant Data Meta-Analysis - Ali, Myzoon; VandenBerg, Kathryn; Williams, Louise R.; Williams, Linda J.; Abo, Masahiro; Becker, Frank; Bowen, Audrey; Brandenburg, Caitlin; Copland, David A.; Worrall, Linda; Breitenstein, Caterina; Bruehl, Stefanie; et al. (My University, 2021)
The factors associated with recovery of language domains after stroke remain uncertain. We described recovery of overall-language-ability, auditory comprehension, naming, and functional-communication across participants' age, sex, and aphasia chronicity in a large, multilingual, international aphasia dataset.
Keywords: Aphasia; Comprehension; Demography; Language; Survivor